Dynamic of soil properties under an exotic pine (Pinus sp.) species growing in Bantaeng Regency. Issue 2 (July 2021) - Mukrimin, M; Ghiffary, M I; Anshari, M F; Gusmiaty, G; Restu, M
Abstract: One of the conifer species that can thrive in Indonesia is Pinus merkusii . This pine is an endemic species on the island of Sumatra, particularly in Aceh, Tapanuli, and Kerinci. In addition, there were other exotic species ( Pinus sp. ) growing on the island of Sulawesi. However, it has never been reported before. Therefore, this study aims to examine and describe the soil characteristics under Rombeng Pine ( Pinus sp. ) stand in Bantaeng Regency in terms of information on the soil nutrients under the Pinus sp . stand. The used method included sampling soil and collecting tree tissues. The results showed that the characteristics of soil properties varied. Both physical and chemical soil characteristics varied, particularly in soil texture class, organic matter content, C%, N%, C/N ratio, P2 O5, and Mg.